The Role of New Innovative Pedagogical Technologies in The Methodology of Teaching Foreign Languages (Eurasian Journal of Humanities and Social Sciences, 2023)
In this article, the types of the role of new innovative pedagogical technologies in the methodology of teaching foreign languages and the issues of their application are considered, and the types of modern methods and the issues of their application are considered